1998
DOI: 10.1046/j.1440-1614.1998.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Mania associated with codeine and paracetamol

Abstract: Mania can be induced by large doses of Panadeine forte, particularly if there is a biological predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Case reports and small clinical studies have suggested that opioid use can induce manic episodes in subjects with pre-existing affective disorders (Shaffer et al, 2007; Watts & Grady, 1997; Gonzalez-Pinto et al, 2001; Orr et al, 1998). While we do not have information on reasons for opioid use among individuals with bipolar disorder (e.g., to self-medicate back pain symptoms-analgesia or simply to “get high”-euphoria), we did find strong and significant associations for an increased risk of opioid use and dependence in the presence of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports and small clinical studies have suggested that opioid use can induce manic episodes in subjects with pre-existing affective disorders (Shaffer et al, 2007; Watts & Grady, 1997; Gonzalez-Pinto et al, 2001; Orr et al, 1998). While we do not have information on reasons for opioid use among individuals with bipolar disorder (e.g., to self-medicate back pain symptoms-analgesia or simply to “get high”-euphoria), we did find strong and significant associations for an increased risk of opioid use and dependence in the presence of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine, for example, decreases REM sleep and SWS, and increases awakenings or arousals (Table 3) [60]. If an opioid is chosen, it is important to observe such patients carefully, because opioids may produce excitation or even mania [65].…”
Section: Treatment Strategies For the Comorbidities Of Chronic Painmentioning
confidence: 99%